Investigating the Relationship Between Type D Personality Characteristics and Self‐Efficacy in Coronary Artery Disease Patients With Type A Personality: A Cross‐Sectional Descriptive Study - Mahnaz Bahrami; Shahnaz Ahrari; Arvin Mirshahi; Mobin Soleimanian Asl; Mohammad Esmaeelzadeh (Health Science Reports)
ABSTRACT Background and Aims Coronary artery disease is one of the chronic diseases that contribute to a significant number of deaths worldwide. The prevention and management of coronary artery diseases are greatly influenced by the lifestyle of patients suffering from these disorders. On the contrary, as the personality types of individuals have the potential to influence lifestyle modifications, this study was conducted to ascertain the relationship between type D personality characteristics and self‐efficacy in patients with coronary artery disease with type A personality. Methods This Cross‐sectional Descriptive Study was conducted among 150 Patients diagnosed with coronary artery disease with type A personality. The data collection tools Included items on demographics, Friedman‐Rosenman Personality types questionnaire, Persian version of the type D personality scale and self‐efficacy scale. Data were analyzed using descriptive and inferential statistics (multiple linear regression analysis and Spearman Correlational Test). The data analysis was conducted using the 16th edition of the Statistical Product and Service Solutions (SPSS16). Results Most of participants were male (57.4%), and the average age was 59.12 ± 11.83 years. The analysis showed lower self‐efficacy significantly correlates with type D personality characteristics (p < 0.001, r = −0.367). According to the linear regression test, if other variables are held constant, for a one‐unit increase in the type D personality characteristics score, the self‐efficacy score decreases by 0.293 (R2 = 0.19, p < 0.001). Conclusion It is crucial to offer training that focuses on boosting self‐efficacy in individuals diagnosed with coronary artery disease who exhibit traits of type A and type D personalities.